Morphological characteristic and truss morphometric analysis of amphidromous goby (‘nike') (Teleostei: Gobiiformes) in Bone River, Gorontalo, Indonesia - NURALIM PASISINGI; DWY SUCI; CITRA PANIGORO; MIFTAHUL KHAIR KADIM (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pasisingi N, Suci D, Panigoro C, Kadim MK. 2024. Morphological characteristic and truss morphometric analysis of amphidromous goby (‘nike') (Teleostei: Gobiiformes) in Bone River, Gorontalo, Indonesia. Biodiversitas 25: 223-231. One of the preferred fish resources in the Gorontalo region is amphidromous goby species, commonly known by local community as nike fish. In rivers, at the adult stage, these fish are morphologically and potentially morphometrically not necessarily distinguishable among species and between sexes. This research aimed to identify the morphological and morphometric truss characters that distinguish the sexual characteristics of goby fishes in the Bone River, Gorontalo. Fish samples were purposefully collected from eight sites along the river, spanning from upstream to downstream, using a backpack electrofishing device. Sampling occurred in March and November 2022, with morphological analysis and measurements conducted on 336 individuals. The morphometric method measured data from 13 points on the sample body, forming 28 combinations of truss distance characters (A1-A3; B1-B12; C1-C10; D1-D3) connecting these points. Morphologically, the samples were identified as three species, namely Sicyopterus longifilis, Belobranchus belobranchus, and Awaous grammepomus. This study revealed distinctions in morphological characters between male and female individuals. In S. longifilis, males exhibited a relatively slimmer body shape compared to the rounded form of females. Male B. belobranchus displayed more striking coloration than females, while male A. grammepomus featured a lighter brown body color than the paler females. All the morphometric truss characters in this study can be reliably used as a sexual distinguishing characteristic in S. longifilis. As for species B. belobranchus, B7 truss cannot be considered a differentiator. In A. grammepomus, thirteen truss characters (B3, B4, B6, B7, B8, B10, B12, C3, C6, C7, C9, C10, D1) cannot be used to differentiate males and females.